The synthetic curcuminoid BHMC restores endotoxin-stimulated HUVEC dysfunction: specific disruption on enzymatic activity of p38 MAPK - Chau, Ling Tham; Harith, Hanis Hazeera; Kok, Wai Lam; Yi, Joong Chong; Cheema, Manraj Singh; Sulaiman, Mohd Roslan; Lajis, Nordin; Ahmad Israf, Daud (Elsevier, 2015)
2,6-bis-(4-hydroxyl-3-methoxybenzylidine)cyclohexanone (BHMC) has been proven to selectively inhibit the synthesis of proinflammatory mediators in lipopolysaccharide-induced U937 monocytes through specific interruption of p38 Mitogen-Activated Protein Kinase enzymatic activity and improves the survival rate in a murine lethal sepsis model. The present study addressed the effects of BHMC upon lipopolysaccharide-induced endothelial dysfunction in human umbilical vein endothelial cells to determine the underlying mechanisms. The cytotoxicity effect of BHMC on HUVEC were determined by MTT assay. The effects of BHMC on endothelial dysfunction induced by lipopolysaccharide such as endothelial hyperpermeability, monocyte-endothelial adhesion, transendothelial migration, up-regulation of adhesion molecules and chemokines were evaluated. The effects of BHMC at transcriptional and post-translational levels were determined by Reverse Transcriptase-Polymerase Chain Reaction and Western Blots. The mode of action of BHMC was dissected by looking into the activation of Nuclear Factor-kappa B and Mitogen-Activated Protein Kinases. BHMC concentration-dependently reduced endothelial hyperpermeability, leukocyte-endothelial cell adhesion and monocyte transendothelial migration through inhibition of the protein expression of adhesion molecules (Intercellular Adhesion Molecule-1 and Vascular Cell Adhesion Molecule-1) and secretion of chemokines (Monocyte Chemotactic Protein-1) at the transcriptional level. BHMC restored endothelial dysfunction via selective inhibition of p38 Mitogen-Activated Protein Kinase enzymatic activity which indirectly prevents the activation of Nuclear Factor-kappaB and Activator Protein-1 transcription factors. These findings further support earlier observations on the inhibition of BHMC on inflammatory events through specific disruption of p38 Mitogen-Activated Protein Kinase enzymatic activity and provide new insights into the inhibitory effects of BHMC on lipopolysaccharide-induced endothelial dysfunction.